Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

While what I'm trying to prove is related to this topic but alas I cannot just assume that given: $ p(x) $ where $ \deg(p(x))=2n+1$ where $n\in\mathbb{N}$ that the only two cases are:

  • $\lim \limits_{x\to -\infty}f(x)=-\infty$ and $\lim \limits_{x\to \infty}f(x)=\infty$


  • $\lim \limits_{x\to -\infty}f(x)=\infty$ and $\lim \limits_{x\to \infty}f(x)=-\infty$

I've tried proving that given that

$ x^{2n+1} $ and $ \sum \limits_{k=0}^{2n}{a_{k}x^k}$, $n\in\mathbb{N}$ and $a_k>1$


$ \exists x_1\in\mathbb{R} , \forall x>x_1 $

$ x^{2n+1} > \sum \limits_{k=0}^{2n}{a_{k}x^k} $

And I think I proved it but it's an ugly inductive proof: for $n=1$

$ x^{3} > a_2x^2+a_1x+a_0 $

then I've tried choosing $x_1 = (a_2a_1a_0)^2 $

then assuming $ x^{2n+1} > \sum \limits_{k=0}^{2n}{a_{k}x^k} $ proving that $ x^{2n+3} > \sum \limits_{k=0}^{2n+2}{a_{k}x^k} $

Which is the same as : $ x^{2n+3} > \sum \limits_{k=0}^{2n}{a_{k}x^k} + a_{2n+1}x^{2n+1}+ a_{2n+2}x^{2n+2} $ and then replace $ \sum \limits_{k=0}^{2n}{a_{k}x^k} $ with $ x^{2n+1} $

meaning : $ x^{2n+3} > x^{2n+1} + a_{2n+1}x^{2n+1}+ a_{2n+2}x^{2n+2} $ and assuming $x\neq0$ dividing by $ x^{2n+1} $ will mean that it's sufficient to show that:

$x^{2} > 1 + a_{2n+1} + a_{2n+2}x $ which is too fairly easy to show.

The problem is I don't know whether showing this is really sufficient ( I intended to use that to show that if for example the coefficient of the highest degree variable is positive that $\forall M\in\mathbb{R} \exists X_1 , x>X_1 \Rightarrow f(x)>M$ ).

So what I'm asking is:

  1. Whether it makes sense at all because it feels like I have holes in my proof.
  2. Is there a more mathematically elegant way to prove this not using derivatives.

Thanks and I deeply apologize if I broke any rule, I've really tried not to.

share|cite|improve this question
up vote 3 down vote accepted

For an elegant approach, the usual method for polynomials and rational functions appearing in limits is to factor out the most significant term. e.g.

$$ \lim_{x \to +\infty} 1 + 2x + x^2 = \lim_{x \to +\infty} x^2 \left(\frac{1}{x^2} + \frac{2}{x} + 1 \right)$$

$$ \lim_{x \to 1} 1 - x - x^2 + x^3 = \lim_{x \to 1} (x-1)^2 \left((x-1) + 2 \right) $$

share|cite|improve this answer
So you propose to write that given the previously mentioned $p(x)$ I can always describe it as $ a_{2n+1}x^{2n+1} + a_{2n}x^{2n} + \cdots + a_{2}x^{2} + a_{0}$ and then just factor it into $ \lim\limits_{x \to +\infty} x^{2n+1} \left(\frac{a_0}{x^{2n+1}} + \cdots + \frac{a_{2n}}{x} + a_{2n+1} \right) $ ? And then using limit properties show that this limit is indeed $\pm\infty$ depending on the sign of $a_{2n+1}$ when $x\to\pm\infty$ ? – Scis Jan 12 '13 at 9:50
Right, that's the general idea. – Hurkyl Jan 12 '13 at 11:07

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.